Deciphering the anti-constipation characteristics of palm dates (Phoenix dactylifera): a review - Emma Camilleri; Renald Blundell; Andrea Cuschieri (International Journal of Food Properties)
Phoenix dactylifera, commonly known as palm dates, is an inexpensive dietary staple in many countries. It is rich in many nutrients and bioactive chemicals, which are responsible for its health benefits. Folk medicine has suggested that P.dactylifera has potent anti-constipation effects. Although many studies have investigated its physiological mechanisms and phytochemistry against diseases like colon cancer, hypertension and diabetes mellitus, research unraveling this fruit’s laxative properties is limited. Studies characterizing the phytochemical, micromolecular and macromolecular composition of Phoenix dactylifera revealed numerous compounds with anti-constipation properties. The flavonoid, phenol, dietary fiber and mineral content were identified as the likely protagonists collectively contributing to Phoenix dactylifera’s laxative properties.